Role of behavioural intention and selective profile on the relationship between behavioural factors and mobile phone usage among paddy farmers in Selangor, Malaysia - Ramli, Nor Sabila (2020)
Agriculture is the backbone of Malaysia’s economy. One of the powerful tools in Information and Communications Technology (ICT) is in this millennium the mobile phone Mobile phone usage has a significant impact on the spread of agricultural information. Undoubtedly, mobile phone plays an active role in the development of agriculture in rural areas. Information is a key component in order to improve production including agricultural production. In order to achieve the success of ICT implementation in development efforts, understanding the impact of social structures on how the technology adopted provides benefits from its use is more important. For this study, a modified Unified Theory of Acceptance and Use of Technology (UTAUT) model was combined with Theory of Planned Behaviour (TPB).